Digital Footprint of Violence: Bibliometric Analysis of Online Gender-Based Violence with Vosviewer and Scopus - Rakhmawati, Dini; Saptadi, Heri; Ratu, Bau; Suryadi; Basir Jarah Anilon (Universitas PGRI Yogyakarta, 2026)
This study aims to map and analyze the scientific landscape of online gender-based violence (OGBV) comprehensively through a bibliometric approach, utilizing the Scopus database and the VOSviewer visualization tool. The goal is to identify trends in topic evolution, key research focus clusters, and prospective research gaps. This method quantifies and visualizes the research structure of OGBV from 2016 to 2025. The results of the Co-Keyword analysis show that the scientific literature is very focused on two main concepts: